Strategi Menjaga Eksistensi Kearifan Lokal Melalui Tari Zapin di Era Globalisasi - Anggela, Dea Resti; Pasaribu, Ester Edenia Br; Santika, Mela Putri; Ningsih, Nurbadria; Havina, Syahmila; Putri, Wartini Arwinda; Hasibuan, Hamdi Abdullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses strategies to maintain the existence of local wisdom through Zapin dance in the era of globalization. As one of Indonesia’s cultural heritages, Zapin dance faces major challenges in maintaining its relevance and sustainability amidst the massive flow of globalization. This study uses literature studies to analyze various relevant sources, including scientific journals, books, and publications related to Zapin dance, local wisdom, and the impact of globalization on culture. The results of the study indicate that adaptive strategies are very important to maintain the local wisdom of Zapin Dance. This strategy includes an educational approach through school curriculum and dance studios, digitalization and online promotion through social media and digital platforms, cultural shortcut collaboration to introduce Zapin dance to a more satisfied audience, and choreographic innovation that still respects tradition without losing its original essence. In addition, strengthening the community of Zapin dancers and preservers is also crucial in creating an ecosystem that supports the sustainability of this dance. By implementing these strategies comprehensively, it is hoped that Zapin dance will not only survive but can also develop and continue to be a strong cultural identity amidst global dynamics.